Lithiation‐Induced Vacancy Engineering of Co3O4 with Improved Faradic Reactivity for High‐Performance Supercapacitor. (30th July 2020) - Zhang, Yu; Hu, Yuxiang; Wang, Zhiliang; Lin, Tongen; Zhu, Xiaobo; Luo, Bin; Hu, Han; Xing, Wei; Yan, Zifeng; Wang, Lianzhou
Abstract: Transition metal oxides are promising electrode candidates for supercapacitor because of their low cost, high theoretical capacity, and good reversibility. However, intrinsically poor electrical conductivity and sluggish reaction kinetics of these oxides normally lead to low specific capacity and slow rate capability of the devices. Herein, a commonly used cobalt oxide is used as an example to demonstrate that lithiation process as a new strategy to enhance its electrochemical performance for supercapacitor application. Detailed characterization reveals that electrochemical lithiation of Co3 O4 crystal reduces the coordination of the CoO band, leading to substantially increased oxygen vacancies (octahedral Co 2+ sites). These vacancies further trigger the formation of a new electronic state in the bandgap, resulting in remarkably improved electrical conductivity and accelerated faradic reactions. The lithiated Co3 O4 exhibits a noticeably enhanced specific capacity of 260 mAh g −1 at 1 A g −1, approximately fourfold enhancement compared to that of pristine Co3 O4 (66 mAh g −1 ). The hybrid supercapacitor assembled with lithiated Co3 O4 //N‐doped activated carbon achieves high energy densities in a broad range of power densities, e.g., 76.7 Wh kg −1 at 0.29 kW kg −1, 46.9 Wh kg −1 at a high power density of 18.7 kW kg −1, outperforming most of the reported hybrid supercapacitors. Abstract : An effective strategy for improving the faradic reactivity of the Co3 O4 electrode material by lithiation‐induced vacancy engineering is presented. Electrochemical tests demonstrate that the lithiated Co3 O4 electrode exhibits a noticeably enhanced specific capacity of 260 mAh g −1 at 1 A g −1, approximately fourfold enhancement compared to that of pristine Co3 O4 (66 mAh g −1 ) and exceptional cyclability.